Preliminary evaluation of the short‐term outcomes of polytetrafluoroethylene mesh for pelvic organ prolapse. Issue 7 (4th May 2021) - Nakai, Kensaku; Hamuro, Akihiro; Kitada, Kohei; Tahara, Mie; Misugi, Takuya; Nakano, Akemi; Koyama, Masayasu; Tachibana, Daisuke
Abstract: Aim: Tension‐free vaginal mesh (TVM) surgery using synthetic polypropylene (PP) soft mesh had spread rapidly. However, the frequency of mesh‐related postoperative complications had increased, and PP was banned in April 2019. In Japan, however, transvaginal surgery using polytetrafluoroethylene (PTFE) mesh had been approved. In this study, we evaluated the clinical outcome and quality of life (QOL) of the postoperative course using PP mesh and PTFE mesh (named "ORIHIME™ " ) in a combination surgery for utero‐sacral ligament suspension and anterior vaginal support using anterior TVM. Methods: The vaginal hysterectomy and utero‐sacral ligament colpopexy augmented by anterior vaginal mesh implants using PP mesh and PTFE mesh were performed on patients with stage III to IV cystocele and uterine prolapse. The clinical outcome and QOL changes in their postoperative course were evaluated by comparing 15 cases of PP mesh and 13 cases of PTFE mesh. Results: There was no difference between the PP group and PTFE group in characteristics. No mesh‐related complications occurred during the follow‐up period. With regard to the pelvic organ prolapse quantification (POP‐Q) score, no significant difference was found between the two groups. Comparing the postoperative QOL of both groups, the PTFE group had significantly higher values in two domains than PP group (SF‐12v2 questionnaire). Conclusions: We used the world's first PTFE mesh to compare PP mesh with postoperative POP‐Q and QOL after the same surgery, with the same operator, and at the same institution. The results showed no significant difference between both mesh materials in the short‐term.